2017
DOI: 10.3389/fnhum.2017.00559
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electro-Acupuncture and Moxibustion on Brain Connectivity in Patients with Crohn’s Disease: A Resting-State fMRI Study

Abstract: Acupuncture and moxibustion have been shown to be effective in treating Crohn’s disease (CD), but their therapeutic mechanisms remain unclear. Here we compared brain responses to either electro-acupuncture or moxibustion treatment in CD patients experiencing remission. A total of 65 patients were randomly divided into an electro-acupuncture group (n = 32) or a moxibustion group (n = 33), and treated for 12 weeks. Eighteen patients in the electro-acupuncture group and 20 patients in the moxibustion group underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…Acupuncture and moxibustion, most popular complementary and alternative therapies, have been used for thousands of years in China [ 7 ]. Currently, they are increasingly used over time because of their lower costs and safety for clinical use [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture and moxibustion, most popular complementary and alternative therapies, have been used for thousands of years in China [ 7 ]. Currently, they are increasingly used over time because of their lower costs and safety for clinical use [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herb-partition moxibustion combined with acupuncture can improve the clinical common symptoms of abdominal pain, diarrhea, fatigue and anorexia for mild and moderate CD [26]. Both treatments of electro-acupuncture and moxibustion improved cortex-subcortical coupling in remissive CD patients, but electro-acupuncture regulated homeostatic afferent processing network, while moxibustion mainly regulated the default mode network [44]. In CD rats, moxibustion can up-regulate the A20 expression level and down-regulate the expression of TNFR1, TRADD, and RIP1, and increase cell apoptosis in the intestinal epithelial barrier [45].…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture and moxibustion treatment showed better overall efficacy than 5-aminosalicylic acid in treating IBD [29]. According to a resting-state functional magnetic resonance imaging (fMRI) study in CD patients, electro-acupuncture and moxibustion mainly modulated the brain homeostatic afferent processing network and default mode network, respectively [30]. These results suggested that electro-acupuncture and moxibustion may help to improve clinical results in CD patients through different central integration patterns.…”
Section: Discussionmentioning
confidence: 99%